2009
DOI: 10.1213/ane.0b013e3181bdc8a0
|View full text |Cite
|
Sign up to set email alerts
|

The Early and Delayed Analgesic Effects of Ketamine After Total Hip Arthroplasty: A Prospective, Randomized, Controlled, Double-Blind Study

Abstract: Ketamine had a morphine-sparing effect after THA, even when morphine was combined with multimodal systemic analgesia. It also facilitated rehabilitation at 1 mo and decreased postoperative chronic pain up to 6 mo after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 37 publications
4
129
1
5
Order By: Relevance
“…58 Ketamine may be especially useful as part of a multimodal analgesic regimen in postsurgical patients with high opioid requirements or opioid-refractory pain. As NMDA receptors are involved in the development of pathological pain states, such as hyperalgesia, ketamine has also been shown to decrease chronic postsurgical pain and opioid consumption after total hip arthroplasty (ketamine 0.5 mgÁkg -1 iv before incision and a 24-hr infusion of 2 lgÁkg -1 Ámin -1 ) 59 and even in opioid-dependent patients undergoing lumbar spine surgery. 59,60 Importantly, the specific use of ketamine for patients with chronic pain, whether perioperatively or otherwise, is currently off-label and not well-studied.…”
Section: N-methyl-d-aspartate (Nmda) Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Ketamine may be especially useful as part of a multimodal analgesic regimen in postsurgical patients with high opioid requirements or opioid-refractory pain. As NMDA receptors are involved in the development of pathological pain states, such as hyperalgesia, ketamine has also been shown to decrease chronic postsurgical pain and opioid consumption after total hip arthroplasty (ketamine 0.5 mgÁkg -1 iv before incision and a 24-hr infusion of 2 lgÁkg -1 Ámin -1 ) 59 and even in opioid-dependent patients undergoing lumbar spine surgery. 59,60 Importantly, the specific use of ketamine for patients with chronic pain, whether perioperatively or otherwise, is currently off-label and not well-studied.…”
Section: N-methyl-d-aspartate (Nmda) Receptor Antagonistsmentioning
confidence: 99%
“…As NMDA receptors are involved in the development of pathological pain states, such as hyperalgesia, ketamine has also been shown to decrease chronic postsurgical pain and opioid consumption after total hip arthroplasty (ketamine 0.5 mgÁkg -1 iv before incision and a 24-hr infusion of 2 lgÁkg -1 Ámin -1 ) 59 and even in opioid-dependent patients undergoing lumbar spine surgery. 59,60 Importantly, the specific use of ketamine for patients with chronic pain, whether perioperatively or otherwise, is currently off-label and not well-studied. Ketamine is U.S. Food and Drug Administration (FDA) approved as a supplement for lowpotency agents (e.g., nitrous oxide) as well as for diagnostic and surgical procedures that do not require skeletal muscle relaxation for induction of anesthesia before the administration of other general anesthetic agents.…”
Section: N-methyl-d-aspartate (Nmda) Receptor Antagonistsmentioning
confidence: 99%
“…Ketamine (a non-competitive NMDA receptor antagonist) is believed to reduce pain and analgesic consumption through the prevention of NMDA-mediated sensitization of spinal cord dorsal horn neurons [46]. Fourteen trials comparing ketamine to placebo for CPSP have been previously identified [11], of which 12 were used in the Chaparro et al [11] systematic review [47][48][49][50][51][52][53][54].The majority of trials identified used pre-incisional loading doses of ketamine ranging from 0.15 to 1 mg/kg, plus an intraoperative infusion. A total cumulative dose of less than 1 mg/kg was reached in 6/14 studies, 4/14 studies administered a cumulative dose of ketamine between 1 and 2 mg/kg, and 4/14 administered a dose greater than 2 mg/ kg [11].…”
Section: Ketaminementioning
confidence: 99%
“…In addition, Ketamine also showed a morphine-sparing effect after THA, even when morphine was combined with multimodal systemic analgesia. Furthermore, Ketamine also facilitated rehabilitation and reduced persistent postoperative chronic pain up to six months after surgery [14].…”
Section: Exogenic Predicting Factorsmentioning
confidence: 95%